Challenges and Solutions in Implementing Inclusive Education at UPT State Elementary School 067250 Medan - Lestari, Nila; Widiyarti, Gemala; Siregar, Nurhafni; Sari, Dwi Novita (Teunuleh Publisher, 2024)
This research is based on the government's policy on inclusive education, to provide adequate educational opportunities and access for children with special needs, regardless of their background and abilities. The aim of this research is to find out how inclusive education is implemented at UPT SDN 067250 Medan. This type of data collection uses descriptive methods, data collection techniques using observation and interviews. Interviews were conducted with school principals and teachers. Observations were made on the learning environment and teachers' teaching activities in the classroom. The findings of this research are that the UPT SDN 067250 school has integrated students with special needs with regular classes, the principal and teachers have also made efforts to create a friendly learning environment for all children and prepare them to be more independent. However, in its implementation there are obstacles to low human resources in dealing with children with special needs, especially class teachers who still need training in implementing inclusive learning in designing programs, providing appropriate learning models, as well as the lack of availability of Special Assistant Teachers (GPK), and inadequate learning facilities. The solution offered is to carry out regular evaluations and determine a framework, as well as the need for cooperation between the city government and schools to provide training for teachers and the school community, as well as providing adequate learning facilities.